1
$\begingroup$

$$\frac{\tan^2(3x)}{1+\tan^2(3x)}+\frac{\tan^2(2x)}{1+\tan^2(2x)}+\frac{\tan^2(x)}{1+\tan^2(x)}=2$$ if we simplify ,we have $$\sin^2(3x)+\sin^2(2x)+\sin^2(x)=2\\\frac{1-\cos(6x)}{2}+\frac{1-\cos(4x)}{2}+\frac{1-\cos(2x)}{2}=2\\ \cos(6x)+\cos(4x)+\cos(2x)=-1\\\cos(6x)+\cos(2x)=-(1+\cos(4x))\\2\cos(4x)\cos(2x)=-2\cos^2(2x)\\\begin{cases}\cos(2x)= 0 \to 2x=\pm\frac{\pi}{2}+k\pi\\\cos(2x)=-\cos(4x)\to \begin{cases}\cos(2x)=-1\\\cos(2x)=\frac12\end{cases}\end{cases},$$ but all of the roots are not acceptable because ,the denominator of $\tan(3x) $ or $ \tan(2x) $ or$ \tan(x) $ going to be zero .
Is my work true ? If draw the $f(x)=\frac{\tan^2(3x)}{1+\tan^2(3x)}+\frac{\tan^2(2x)}{1+\tan^2(2x)}+\frac{\tan^2(x)}{1+\tan^2(x)}$ and $g(x)=2$ by desmos ...we will see some roots $\frac{\pi}{6} ,\frac{\pi}{2} $ are recognizable ,but what about the other ?
https://www.desmos.com/calculator/x9ikgkbyhp

$\endgroup$
0
$\begingroup$

I think you are right and our equation has no solutions.

"Roots" $a$ which you see they are because $$\lim_{x\rightarrow a}\left(\frac{\tan^23x}{1+\tan^23x}+\frac{\tan^22x}{1+\tan^22x}+\frac{\tan^2x}{1+\tan^2x}\right)=2.$$ It follows from your solution, but the domain says that they are not roots.

$\endgroup$
0
$\begingroup$

The problem here is that whoever has produced this problem has constructed a form for $sin^2(x)$ which is artificial for the purpose of the puzzle.

It therefore seems like there is a problem.

But there is not because the everywhere in $\mathbb{R}$ the expression involving $tan(x)$ is always going to reduce to $sin^2(x)$.

The artificiality of using $tan(x)$ is a red herring.

It would be like defining $x$ as $\frac {x^2}{x}$ and then claiming there was a singular point at $x=0$ (which there is not).

$\endgroup$
0
$\begingroup$

Suppose otherwise there exists $x\in{\bf R}$ such that $$ \frac{\tan^2(3x)}{1+\tan^2(3x)}+\frac{\tan^2(2x)}{1+\tan^2(2x)}+\frac{\tan^2(x)}{1+\tan^2(x)}=2. $$ If we simplify (using the formula $\sin^2a+\cos^2a=1$ for each term), we have $$\sin^2(3x)+\sin^2(2x)+\sin^2(x)=2\\ \Rightarrow \frac{1-\cos(6x)}{2}+\frac{1-\cos(4x)}{2}+\frac{1-\cos(2x)}{2}=2\\ \Rightarrow \cos(6x)+\cos(4x)+\cos(2x)=-1\\ \Rightarrow\cos(6x)+\cos(2x)=-(1+\cos(4x))$$ which implies that (this step is too quick for me, I don't see why (*) is obviously true.) $$ 2\cos(4x)\cos(2x)=-2\cos^2(2x)\tag{*} $$ $$\tag{**} \begin{cases} \cos(2x)= 0 \to 2x=\pm\frac{\pi}{2}+k\pi\\ \cos(2x)=-\cos(4x)\to \begin{cases}\cos(2x)=-1\\ \cos(2x)=\frac12 \end{cases} \end{cases}, $$ (Too quick. Why does $\cos(2x)=-\cos(4x)$ imply the values you claim in (**)?) but all of the roots are not acceptable because, the denominator of $\tan(3x) $ or $ \tan(2x) $ or $\tan(x) $ going to be zero. ($\cos(2x)=0$ certainly gives a contradiction. How do $-1$ or $1/2$ do so?)


Is my work true? (Unclear. You don't have obvious logic mistakes but proof for several important places is missing.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.